2011
DOI: 10.1042/bj20110114
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-kinase signalling pathway involvement in a truncated apoptotic cascade associated with motility loss and oxidative DNA damage in human spermatozoa

Abstract: Human spermatozoa are characterized by poor functionality and abundant DNA damage that collude to generate the high incidences of male infertility and miscarriage seen in our species. Although apoptosis has been suggested as a possible cause of poor sperm quality, the ability of these cells to enter an apoptotic state and the factors that might trigger such an event are unresolved. In the present study we provide evidence that the commitment of these cells to apoptosis is negatively regulated by PI3K (phosphoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
189
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(197 citation statements)
references
References 60 publications
4
189
0
4
Order By: Relevance
“…Several authors have suggested the involvement of sperm apoptosis in impaired men's fertility with consequences for reducing sperm fertilizing potential [97][98][99]. Mature spermatozoa have been reported to express distinct markers of early and late apoptosis-related cell damage, including the externalization of phosphatidylserine (PS) from the inner to the outer membrane, caspase activation, the loss of mitochondrial membrane potential (∆ym), and DNA fragmentation [96]. According to a novel theory regarding apoptotic process in mature spermatozoa, the increase in the production of ROS by the mitochondria is one of the first signs of intrinsic apoptosis.…”
Section: Apoptosis/necrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have suggested the involvement of sperm apoptosis in impaired men's fertility with consequences for reducing sperm fertilizing potential [97][98][99]. Mature spermatozoa have been reported to express distinct markers of early and late apoptosis-related cell damage, including the externalization of phosphatidylserine (PS) from the inner to the outer membrane, caspase activation, the loss of mitochondrial membrane potential (∆ym), and DNA fragmentation [96]. According to a novel theory regarding apoptotic process in mature spermatozoa, the increase in the production of ROS by the mitochondria is one of the first signs of intrinsic apoptosis.…”
Section: Apoptosis/necrosismentioning
confidence: 99%
“…One novel concept suggests that mitochondrial ROS generation may decide whether spermatozoon remains alive or enters an apoptotic state; its role in the aetiology of male infertility has most recently been postulated in the literature [96].…”
Section: Role Of Oxidative Stressmentioning
confidence: 99%
“…L-amino acid oxidase mitochondrial ROS generation ( Fig. 7; Koppers et al 2011, Aitken et al 2012. The ability of aromatic amino acids, such as phenylalanine, to stimulate the sustained generation of low levels of ROS in human spermatozoa may be of significance in an assisted conception context for the enhancement of IVF rates.…”
Section: Discussionmentioning
confidence: 99%
“…6). This loss of functionality after prolonged exposure to high doses (10 mM) of phenylalanine was associated with the induction of sperm apoptosis as evidenced by statistically significant increases in two hallmarks of this process, mitochondrial ROS generation (Koppers et al 2011), and caspase activation (Fig. 7).…”
Section: Functional Consequences Of Laao Activitymentioning
confidence: 99%
“…OGG1 removes these base adducts creating an abasic site that so destabilises the DNA backbone that fragmentation occurs. Endonuclease-mediated cleavage of DNA cannot occur in spermatozoa because the sperm nucleus is physically separated from the mitochondria and a majority of the cytoplasm (Koppers et al 2011).…”
Section: Obesitymentioning
confidence: 99%